ANALISIS MORFOFONEMIS CASUAL SPEECH PADA KOMIK AISHIIRUDO VOLUME 1 - Anita Soegiharto; Irma Winingsih (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2017)
This study is aimed at describing the morphophonemic analysis of the casual speech on the Aishiirudo 21 comic volume 26. This qualitative research uses Aishiirudo Comic 21 volume 26 as the source of the data. The data are in the form of 99 words belonging to casual speech. The data were analyzed using the framework proposed by Sutedi (2004: 118) by using the following steps: identifying the words belonging to casual speech, the morphophonemic processes of the words. The results showed that there are 4 morphophonemic processes found in the comic, they are 5 assimilation, 57 vowel combining, 19 vowel deletion, and 17 abbreviation. Keywords: Assimilation, Casual Speech, Morphophonemis process, vowelÂ